Mobile genetic elements and wastewater treatment: contaminants of emerging concern, climate change, and trophic transmission - Bradshaw, Aaron (Frontiers in Microbiology, 2025)
This minireview focuses on recent developments regarding mobile genetic elements (MGEs) and horizontal gene transfer (HGT) in wastewater treatment plants (WWTPs) and proximal environments. WWTPs are often discussed as hotspots and bioreactors for the evolution of MGEs and ARGs and their horizontal transfer. Firstly, the article reviews the effects of emerging contaminants on HGT and MGEs with a specific focus on microplastics and per- and polyfluoroalkyl substances (PFAS). Secondly, the review focuses on how extreme weather and climate change can overwhelm WWTPs, increase the input of diverse genetic elements, and alter the dynamics of HGT. Finally, the trophic connections between the WWTP microbiota and external ecosystems underscore the potential for wider transmission of MGEs. Here, the focus is on transfer of MGEs to larger organisms in the vicinity of WWTPs. In sum, the review focuses on emerging areas of research that refine our understanding of the WWTP environment as a hotspot for HGT and dissemination of MGEs with potentially deleterious implications for human and wider ecosystem health.